Aligning Skills with Industry 4.0: An Exploratory Study of IT Workforce Challenges in Kerala, India - Oommen, Jishin George; Manimekalai, M.; Roy, Noel Simon; Nithya, U. S. (International Review of Management and Marketing, 2025)
The swift development of digital technologies has brought Industry 4.0 to life, revolutionizing industrial processes and expectations from the workforce. Along with the evolution of the global IT industry through innovations like artificial intelligence (AI), machine learning (ML), internet of things (IoT), cloud computing, and cyber-physical systems (CPS), it has become the need of the hour to synchronize workforce skills with these technological requirements. This research investigates the difficulties of IT professionals in Kerala in adopting Industry 4.0, emphasizing determining skill gaps, assessing training effectiveness, and determining organizational readiness. Adopting an exploratory and descriptive research approach, the research surveyed 410 IT professionals from different places of Kerala, a state of India using structured questionnaires. Statistical analysis was done using t-test, ANOVA, Chi-square, correlation, and regression through SPSS and Excel. The results demonstrate a moderate level of awareness of Industry 4.0 concepts but huge disparities in applied skills, especially among middle-career workers. The available academic curriculum and training programs were deemed not to be properly aligned with industry demands. The study highlights the need for cooperation between academia, industry, and government to update training schemes and embed Industry 4.0 technologies in mainstream education. Strategic efforts in skill enhancement, ongoing learning, and curriculum change are required to make Kerala’s IT talent pool competitive and future-fit in the age of digital technology.